Maternal Serum Zinc level in pregnant women with second trimester induced abortion with anencephalic fetus - Shalal, .Maad M.; Al-Bassam, Anwar N.; Alwan, Buthaina A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Neural tube defects (NTD) are group of heterogeneous and complex congenital anomalies of the CNS. Commonly included in this group anencephaly, spina bifida andencephaloceles. Anencephaly is the most severe defect; it is always lethal and results in stillbirth or early neonatal demise, is characterized by absence of the brain and cranium above the base of the skull and orbitsObjective: The objective of this study is to assess the relationship between maternal serum zinc level and anencephaly occurrence in women with second -trimester induced abortion due to anencephalic fetus.Study design and setting: This study is a case- control study, carried out in Baghdad teaching hospital throughout the period between November 2008- November 2009.Patients and method: This study involves 33 pregnant women whose pregnancies were terminated for anencephaly in the second-trimester that was diagnosed by ultrasound the control group consisted of 66 matched to demographic and obstetrical characteristics and had normal ultrasonographic findings in second-trimester with documented normal fetal outcome. Zinc level determination was made using flame atomic absorption spectrophotometer (AAS).Results: Medication consumption during the first trimester of pregnancy has a significant relation with the occurrence of NTDs with a p – value = 0.027. Low serum Zinc level was found in 18 (54.5%) of the cases and 5 (7.6%) of the controls with p- value = 0.0001. There was a highly significant relationship between the presence of NTDs and low serumzinc level.Conclusions: In this study there was a significant association between NTDs and low serum zinc levels, adding to the evidence about the importance of nutritional and maternal health factors in the etiology of this disease.